Human Papillomavirus E6 biosensing: current progression on early detection strategies for cervical cancer - Parmin, Nor Azizah; Hashim, Uda; Gopinath, Subash Chandra Bose; Sharifah Nadzirah; Rejali, Zulida; Mohd Jamil, Amilia Afzan (Elsevier BV, 2019)
Prognosis of early cancer detection becomes one of the tremendous issues in the medical health system. Medical debates among specialist doctor and researcher in therapeutic approaches became a hot concern for cervix cancer deficiencies early screening, risk factors cross-reaction, portability device, rapid and free labeling system. The electrical biosensing based system showed credibility in higher specificity and selectivity due to hybridization of DNA duplex between analyte target and DNA probes. Electrical DNA sensor for cervix cancer has attracted too many attentions to researcher notification based on high performance, easy to handle, rapid system and possible to miniaturize. This review explores the current progression and future insignificant for HPV E6 genobiosensing for early Detection Strategies of Cervical Cancer.